Translation Strategies Used By EFL Students In Kefamenanu - Theresia Ngawul; Thresia Trivict Semiun; Merlin Helentina Napitupulu (Jurnal Pendidikan LLDIKTI Wilayah 1 (JUDIK), 2024)
Translation is commonly done by the students in the classroom. This study aims to figure out the students’ strategies, the students’ problems, and the students’ level of mastery in translating Indonesian descriptive text into English. The object of the study was the second grade students of sciences major SMA Swasta Pelita Karya Kefamenanu. The class consisted of 25 students. In this study, the researcher applied qualitative and quantitative methods to analyze and identify strategies, problems, and students’ levels of mastery in translating the descriptive text. The research results revealed that first, the strategies used by the students to translate the descriptive text were adaptation, borrowing, and literal translation. Second, problems faced by the students in translating the descriptive text were that the text was considered long but the time to do the translation was not enough. Most of the students didn’t have dictionaries and were lack of vocabularies, so they could not translate the text correctly. Third, the students’ ability for translating the descriptive text was good.